Pattern of fluid consumption in a sample of Saudi Arabian adolescents aged 12–13 years - L. L. BELLO & N. AL-HAMMAD (Paediatric Dentistry, 2006)
To study the pattern of fluid consumption in a group of Saudi adolescent boys and girls aged 12–13 years.